2010
DOI: 10.1007/s00405-010-1418-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine in otorhinolaryngology: what does the future hold?

Abstract: Nanotechnology and nanomedicine are new and rapidly developing areas which are concerned with the utilisation of structures and devices, one billionth of a metre in scale and how their special properties may be utilised in the diagnosis and treatment of diseases. In otorhinolaryngology, there have been some inroads into utilising these new treatment modalities and there is future prospect for significant developments. Their impact may be to revolutionise the current practice of otorhinolaryngology. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Kim Figure 1 Nanochart showing relative scales of nanosized items to everyday objects [1] . Permission/license was obtained from RightsLink; license number: 3091760162166.…”
Section: Goldmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim Figure 1 Nanochart showing relative scales of nanosized items to everyday objects [1] . Permission/license was obtained from RightsLink; license number: 3091760162166.…”
Section: Goldmentioning
confidence: 99%
“…The term " nanoparticles " usually refers to solid particles between 1 and 100 nm in diameter ( Figure 1 ) [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the properties of NPs, [15][16][17]150,151 complex adaptive systems models for homeopathic medicine interactions with the individual patient; 84,85,88,92,94,108 and nonlinear doseresponse effects at low doses of substances 23,100,152,153 are also emerging as major frontiers in conventional medical research. 22,[154][155][156][157][158][159][160][161][162][163][164] An appropriately conservative conclusion is that the effectiveness data are more extensive than the efficacy data for homeopathic medicines in AOM 129,141 and URIs to date. Additional, appropriately-designed efficacy studies with not only good internal but also external and model validity are indicated.…”
Section: Limitationsmentioning
confidence: 99%
“…1,2 Nanomedicine describes the application of these technologies to diagnose and treat patients at the molecular level. 3 The unique properties of nanomaterials and nanoparticles (NPs) offer promising applications to patient care. Due to their small size, NPs can cross biological barriers that are otherwise inaccessible to traditional therapies.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Finally, systemic toxicity of modern chemotherapies and immunotherapies may be reduced by targeted therapy. 8 Although articles have summarized the role of nanotechnology in the field of otolaryngology, 3,9,10 some time has passed since the last contemporary review. The purpose of this article is to describe the current standing of nanotechnology relating to drug delivery and diagnostic mechanisms in otolaryngology and the otolaryngological subspecialties.…”
Section: Introductionmentioning
confidence: 99%